Soil Fertility Level In The Aek Kundur River Area Regardless Of Factory Waste Disposal - Surya Ramadani Pane, Risky; Lestari , Widya; Walida , Hilwa; Hariyati Adam , Dini (International Journal of Science, Technology & Management, 2024)
Soil fertility is the ability of the soil to provide the nutrients needed by plants in adequate quantities and in a form that can be absorbed by plant roots. The aim of this research is to determine the level of soil fertility in the Aek Kundur river area regarding factory waste disposal in Lingga Tiga Village, District. West Bar. This research was carried out in June 2024 in Lingga Tiga Village, Bilah Hulu District, Labuhanbatu Regency with an altitude of 28 meters above sea level with coordinates N: 98022'44.34" E: 02032'34.23". Analysis of the physical and chemical properties of soil was carried out at the Laboratory of the Faculty of Agriculture, University of North Sumatra using an exploratory-descriptive survey method. Research results on the physical properties of the soil in Lingga Tiga Village have a clayey clay texture and in Liga Tiga Village have a clay texture. Furthermore, the chemical properties of the soil in Lingga Tiga Village have criteria, namely neutral pH, low organic C, moderate P2O5 and low soil fertility status in the Aek Kundur river area against factory waste disposal. For this reason, fertilization treatment is needed to improve soil fertility status.